2017
DOI: 10.1590/1413-785220172506174033
|View full text |Cite
|
Sign up to set email alerts
|

Mid-Long Term Results of Manipulation and Arthroscopic Release in Frozen Shoulder

Abstract: Objective:Surgical treatment options should be discussed in cases of frozen shoulder, which is usually treated in a conservative manner. In this study, we evaluated the efficacy of manipulation and arthroscopic release in cases of frozen shoulder which resisted conservative treatment. Methods:A total of 32 patients who underwent manipulation and arthroscopic capsular release in 34 shoulders were included in the study. The average follow-up period was 49.5 months (range: 24-90 months). No reason for onset could… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 19 publications
(16 reference statements)
0
4
0
Order By: Relevance
“…7,20 Previous reports mention that type 1 diabetics are at increased risk of having frozen shoulder than type 2 diabetes mellitus. 3,21 Patients with higher HbA1C levels or when diabetes mellitus has been present for a long period (>13 years), are at increased risk for developing adhesive capsulitis. 22,23 Ando and coauthors, in a comparative study, showed excellent clinical results of MUA both in the idiopathic and diabetic frozen shoulders, however poor outcome recorded in diabetic group in comparison with idiopathic group.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…7,20 Previous reports mention that type 1 diabetics are at increased risk of having frozen shoulder than type 2 diabetes mellitus. 3,21 Patients with higher HbA1C levels or when diabetes mellitus has been present for a long period (>13 years), are at increased risk for developing adhesive capsulitis. 22,23 Ando and coauthors, in a comparative study, showed excellent clinical results of MUA both in the idiopathic and diabetic frozen shoulders, however poor outcome recorded in diabetic group in comparison with idiopathic group.…”
Section: Discussionmentioning
confidence: 99%
“…These findings correlate with other reports. 3,18 It shows that frozen shoulder affects females more than males and frequently involves the patients of 4 th to 6 th decades. 1 Codman reported frozen shoulder difficult to define, difficult to treat and difficult to explain in term of pathology.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…, humeral fracture, glenohumeral dislocation, and brachial plexus injury)[ 3 , 8 ]. Therefore, performing an arthroscopic capsular release before a shoulder manipulation is suggested to decrease the incidence of complications[ 3 , 9 , 10 ]. However, some surgeons still prefer to perform the manipulation before arthroscopy to facilitate the performance of the arthroscopy, and the use of an arthroscope after manipulation could increase the release and address any concomitant problems[ 9 - 12 ].…”
Section: Introductionmentioning
confidence: 99%